ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENYERAPAN ANGGARAN BELANJA PADA PEMERINTAH PROVINSI NUSA TENGGARA TIMUR - Melda Mariana Poeh; Giska Ndun; Darwin Yopie Kefi; Septia Sakalini Dioh (P3M- Politeknik Negeri Kupang, 2021)
The purpose of this study is to analyze the factors that influence the absorption of the budget in the East Nusa Tenggara Provincial Government. The research sample is respondents who hold positions in fields related to the budget, including paying officials and operating expenses at SKPD in NTT Province. This study uses quantitative analysis with multiple linear regression analysis tools. The results of this study indicate that there is a positive and significant influence of human resources and the procurement of goods and services on the absorption of the East Nusa Tenggara Provincial Government's budget, while planning has a positive correlation but no significant effect on the absorption of the East Nusa Tenggara Provincial government's budget. The significant level planning variable (0.276 > 0.005) is more than the significant limit so that it can be said to be a rejected variable, the level of human resources (0.000 < 0.005) is less than significant so that bid 2 is accepted, the significant variable is the procurement of goods and services (0.000 < 0.005) < 0.005) is less than the significant limit so that 3 is confirmed to be accepted, and the F test results with a significant value of 0.000 (p < 0.05). Thus it can be said that planning, human resources and procurement of goods and services simultaneously affect the absorption of the budget.